The sample size debate: response to Norman Blaikie. Issue 5 (3rd September 2018) - Sim, Julius; Saunders, Benjamin; Waterfield, Jackie; Kingstone, Tom
ABSTRACT: In his detailed response to our paper on sample size in qualitative research, Norman Blaikie raises important issues concerning conceptual definitions and taxonomy. In particular, he points out the problems associated with a loose, generic application of adjectives such as 'qualitative' or 'inductive'. We endorse this concern, though we suggest that in some specific contexts a broad categorization may be more appropriate than a more nuanced distinction – provided that it is clear in which sense the terms are employed. However, other concepts, such as saturation, do not lend themselves to generic use, and require a more detailed conceptualization. Blaikie's analysis also makes it clear that meaningful discussion of sample size in qualitative research cannot occur with reference to an undifferentiated conception of the nature of qualitative research; clear distinctions need to be made within this approach in terms of methodology, ontological and epistemological assumptions and broader research paradigms.